Determinants of tax non-compliance among small medium enterprises in Malaysia - Okin, Felicia (2019)
Tax non-compliance issue is not new as it has long existed in tandem with the existence of tax, which if not addressed, will affect the collection of tax revenue that is important to the government for development. Although many studies on tax non-compliance were conducted in the past, there are still limited studies that utilized actual tax audit data to identify the relationship between company characteristics and tax noncompliance. Therefore, this study is conducted to identify factors that may be associated to tax non-compliance such as financial liquidity, capital intensity, size of tax agent, type of industry, company size and company ownership among small and medium enterprises (SMEs) in Malaysia. This study uses audit tax adjustment after field audit as a proxy to tax non-compliance. The sample of this study consists of field audits cases for the year of assessment 2016. The regression analysis showed that only company size has a positive and significant relationship to tax non-compliance. The results obtained from this study can be used to improve the existing policies and regulations to address tax non-compliance. Also, the results obtained can be used by the IRBM to understand the determinants of tax non-compliance.